New Solutions of Radial Teukolsky Equation Via Transformation to Heuns Equation with the Application of Rational Polynomial of at Most Degree 2 (Global Journal of Science Frontier Research, 2016)
Abstract not found
Keywords: heun equation; teukolsky equation; type-d metrics; polynomial solutions